High-thermal-conductivity and high-plasticity extruded magnesium alloy and preparation method thereof
By adjusting the proportion of elements such as Al, Zn, RE, Y in magnesium alloys, and controlling the type, size and morphology of the second phase, the problem of insufficient thermal conductivity and strength matching of traditional magnesium alloys is solved, and a magnesium alloy material with high thermal conductivity and high strength toughness is achieved, which is suitable for 5G communications, 3C and automotive industries.
Patent Information
- Application Number
- CN202411724726.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional magnesium alloys have shortcomings in thermal conductivity and strength matching, which limits their application in situations where high heat dissipation and high stress tolerance are required.
By changing the proportion of elements such as Al, Zn, RE, Y in the magnesium alloy, the type, size and morphology of the second phase in the alloy are regulated, and the second phase with a diffuse distribution is used to achieve a good match between thermal conductivity and mechanical properties.
It has achieved high thermal conductivity (>90W/(m·K) and high strength and toughness (yield strength >200MPa, elongation >20%) of magnesium alloy, expanding its application in 5G communication, 3C and automotive industries.
Smart Images

Figure CN119553157A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium alloy material preparation, and in particular to a method for preparing a high-thermal-conductivity and high-plasticity extruded magnesium alloy. Background Art
[0002] Magnesium is the lightest metal structural material with a density of only 1.7g / cm 3 , about 2 / 3 of aluminum and 1 / 4 of steel, with the characteristics of high specific strength and specific stiffness. At the same time, magnesium alloy also has high damping performance and electromagnetic shielding performance. It is a structural-functional integrated material with great development potential and is widely used in aerospace, 3C, 5G communications and automotive fields. Traditional magnesium alloys have deficiencies in thermal conductivity and strength matching, which limits their application in occasions that require high heat dissipation and withstand high stress environments, such as electronic equipment heat dissipation components, automotive engine parts and aerospace structural parts. The thermal conductivity of commercial AZ31 alloy is about 96.4W / (m·K), and the thermal conductivity of commercial die-cast AZ91 and AM60 magnesium alloys is 51.2W / (m·K) and 60.6W / (m·K), respectively. In comparison, the thermal conductivity of pure magnesium at room temperature is about 154.5W / (m·K), but its low mechanical properties cannot meet actual needs. Theoretically, the thermal conductivity of metal materials is determined by the transfer of electrons and phonons inside them, so the fewer crystal defects, the less obstacles the carriers will encounter during heat conduction. Conventional strengthening methods, such as fine grain strengthening, dislocation strengthening, and solid solution strengthening, will more or less reduce their thermal conductivity. In order to coordinate the matching of thermal conductivity and strength, a strategy of dispersing a highly thermally conductive second phase in the magnesium matrix can be adopted. However, a coarse second phase will split the matrix and lead to deterioration of mechanical properties. Therefore, the purpose of simultaneously improving thermal conductivity and strength can be achieved by reducing the size of the second phase and increasing its volume fraction.
[0003] CN117026036A discloses "a high thermal conductivity and high strength deformable magnesium alloy and its preparation method", which belongs to the Mg-Mn-X alloy system, and its composition is 0.5-5.0wt% light rare earth elements, Mn content is 0.5-4.0wt%, and the balance is Mg and inevitable impurities. The yield strength of the alloy can reach more than 380MPa, the thermal conductivity is greater than 120W / (m·K), the strength and thermal conductivity are well matched, but the elongation is less than 6%. CN116657009A discloses "a high strength and high thermal conductivity magnesium alloy and its preparation method", and its composition is Zn: 5.0-8.0wt%, Al: 0.5-3.0wt%, Cu: 0.5-3.0wt%, Zr: 0.1-1.0wt%, Mn: 0-1wt%, Sr: 0-1wt%, La: 0.5-3wt%, Ce: 0.5-3wt%, and the balance is Mg and inevitable impurities. The alloy has a thermal conductivity of 125-135 W / (m·K), a yield strength of 192-216 MPa, and an elongation of 7-10%. The strength and thermal conductivity are well matched, but the elongation is less than 10%. CN109136699B discloses "high thermal conductivity magnesium alloy, inverter housing, inverter and automobile", whose composition is Al: 2.0-4.0 wt%, Mn: 0.1-0.3 wt%, La: 1.0-2.0 wt%, Ce: 2.0-4.0 wt%, Nd: 0.1-1.0 wt%, Zn: 0.5-2.0 wt%, Ca: 0.1-0.5 wt%, Sr≤0.1 wt%, Cu:≤0.1 wt%, and the balance is Mg. The alloy has a thermal conductivity of more than 110 W / (m·K), a yield strength of slightly less than 160 MPa, and an elongation of only 5%.
[0004] In recent years, the demand for high thermal conductivity and high plasticity magnesium alloys has become increasingly urgent. For example, notebook computer shells, mobile phone shells, and automobile center console back panels all require consideration of both thermal conductivity and comprehensive mechanical properties to ensure that the products have high stability and service life. In order to overcome the shortcomings and deficiencies of the prior art, the purpose of the present invention is to use a dispersed second phase to achieve a good match between thermal conductivity and mechanical properties. Summary of the invention
[0005] In view of the above-mentioned deficiencies, the present invention proposes an extruded magnesium alloy material with high thermal conductivity and high plasticity and a preparation method thereof. By changing the proportions of elements such as Al, Zn, RE, Y in the magnesium alloy, the type, size and morphology of the second phase in the alloy are regulated, thereby enhancing the thermal conductivity and toughness of the alloy, and expanding the application of magnesium alloys in 5G communications, 3C and automotive industries.
[0006] In order to solve the above technical problems, the present invention adopts the following technical means:
[0007] The present invention first discloses an extruded magnesium alloy material with high thermal conductivity and high plasticity, comprising the following raw materials in percentage by mass:
[0008] Al 3.0-6.0wt%, Zn 1.0-2.0wt%, Mn 0.5-1.0wt%, RE 0.5-4.5wt%, Y 0.5-4.5wt%, RE+Y 1.0-5.0wt%, the balance being Mg and unavoidable impurities; wherein:
[0009] The total amount of unavoidable impurities ≤ 0.04%;
[0010] Mn, RE and Y are added in the form of MnCl2, mixed RE and Mg-30%Y master alloy respectively.
[0011] Furthermore, the mixed RE has a purity of >99%, and comprises: 35 wt % of La and 65 wt % of Ce.
[0012] The present invention also discloses a method for preparing the above-mentioned extruded magnesium alloy material with high thermal conductivity and high plasticity, comprising the following steps:
[0013] (1) Ingredients: Al ingot, Zn ingot, MnCl2, mixed rare earth, Mg-30% Y master alloy and Mg ingot are prepared according to weight percentage and dried in a drying oven. If water vapor is found on the surface, it cannot be put into the furnace; the crucible is cleaned and prepared for loading into the furnace;
[0014] (2) Melting: Set the furnace temperature to 780℃, put in Mg ingots to keep them warm and melt. During the melting process, add a heat preservation cover or other heat preservation devices to prevent heat loss and oxidation. Carefully operate the melting of the charge, and use CO2+SF6 mixed gas for full protection during the melting process. If white smoke and bright light are found, it means the charge is burning, and immediately sprinkle 2# solvent; after the charge is completely melted, remove the surface scum, remove the lower sediment, and evenly sprinkle a layer of 2# solvent on the upper surface to prepare for alloying; during the melting process of the charge, bridging is prohibited, and once discovered, it must be handled in a timely manner;
[0015] (3) Alloying: When the temperature is raised to 750°C, scouring is performed for 3 minutes. Note that the bottom of the pot should be stirred evenly. After scouring, let it stand for 3 minutes, take out samples for spectral analysis, and keep records (including time, temperature, and amount added). According to the results, alloy the ingredients and keep small samples for subsequent re-testing. When the alloy liquid temperature is 750°C, sprinkle the weighed MnCl2 onto the surface of the melt. After the MnCl2 is melted, use a stirring tool to stir while sprinkling No. 2 flux for alloying. Stir for 3 minutes. After the addition is completed, take out samples for spectral analysis and keep records. (including time, temperature, and amount added), and retain a small sample for subsequent retesting; when the alloy liquid temperature is 740°C, place the weighed Al ingot and Zn ingot in the middle of the melt surface to melt, add the Al ingot and Zn ingot, take out the sample for spectral analysis and keep a record (including time, temperature, and amount added), and retain a small sample for subsequent retesting; when the alloy liquid temperature is 760°C, place the mixed rare earth and Mg-30%Y master alloy in the melt to melt, and obtain a rough alloy sample; take out the sample for spectral analysis and keep a record (including time, temperature, and amount added), and retain a small sample for subsequent retesting;
[0016] (4) Refining: Set the refining temperature to 760°C and continue refining for 5 minutes until the alloy liquid becomes shiny after refining.
[0017] (5) Iron reduction: The alloy liquid is cooled to 680-700℃, and a small amount of No. 2 flux is sprinkled into it to cover it while stirring, and the upper surface of the alloy liquid is not damaged as much as possible;
[0018] (6) Standing and casting: After refining, remove the surface scum, evenly sprinkle a layer of 2# flux, stand for 25-35 minutes, and cast after the composition is qualified; clean the inner wall of the mold before casting, and blow it with SF6 for protection; hydraulic dumping should be done slowly so that the liquid flows into the inner shovel of the mold to prevent external debris from hurting people. When the molten liquid flows to the edge of the large diameter, stop casting, and the casting is completed. After the crucible solution is cast, clean the pot and wait for the next pot of smelting;
[0019] (7) Heat treatment: Place the cast rod in a heat treatment furnace, keep it at 350°C for 24 hours, and then air cool it;
[0020] (8) Extrusion: Use a sawing machine to cut off the loose layer of casting including the head and tail, and use a lathe to turn off the oxide layer on the outer surface of the cast rod. Place it in a heat treatment furnace and preheat it at 300-400°C for 2-4 hours for extrusion. The extrusion ratio is (10-20):1 and the extrusion speed is 0.05-1mm / s.
[0021] Furthermore, the impurity element requirements of the Mg ingot in the raw material of step (1) are Fe≤0.004%, Si≤0.03%, Ni≤0.0006%, Cu≤0.002%; the impurity element requirements of the Al ingot are Fe≤0.12%, Si≤0.06, Ni≤0.015%, Cu≤0.004%; the impurity element requirements of the Zn ingot are Fe≤0.001%, Cu≤0.002%; the purity of MnCl2 is ≥96%, Ni≤0.01%.
[0022] Furthermore, the drying temperature in step (1) is 200-250° C., and the drying time is ≥30 min;
[0023] Furthermore, the basic components of the 2# flux in steps (2) and (5) are 38±3% MnCl2, 37±3% KCl, 9±3 BaCl2, 5±1% CaCl2, and 10±3% NaCl.
[0024] Furthermore, the 2# flux needs to be sieved through a 100-mesh sieve before use, and the sieving rate is ≥50%.
[0025] Furthermore, CO2+SF6 mixed gas is used for protection throughout the smelting process, wherein the CO2 content is 99% and the SF6 content is 1%.
[0026] The invention also discloses an extruded magnesium alloy material with high thermal conductivity and high plasticity prepared according to any one of the above preparation methods.
[0027] The beneficial effects of the present invention are:
[0028] The extruded magnesium alloy produced by the method of the present invention contains La, Ce and Y rare earth strengthening alloying elements. During the smelting process, the rare earth elements are squeezed into the liquid phase at the crystallization front due to solute redistribution, resulting in supercooling of the solidification front components, inhibiting the growth of the grains and refining the casting grains; secondly, the formed Al-RE phase consumes the Al element in the melt, so that the β-Mg17Al12 phase changes from a continuous eutectic morphology to a discontinuous distribution, and the size is reduced, which reduces the splitting effect of the β phase on the matrix. In addition, the addition of rare earths will increase the fluidity of the melt and reduce the casting defects of the cast rods. After extrusion, the grains undergo a recrystallization process, the Al-RE phase is distributed in a band, and the uniformly dispersed second phase ensures high thermal conductivity. The yield strength, elongation and thermal conductivity of the extruded magnesium alloy reach 200MPa, 20% and 90W / (m·K) respectively, which is suitable for promotion and use in 3C, 5G communications and automotive fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a 200x scanning electron microscope micrograph of the alloy obtained in Example 1;
[0030] Figure 2 This is a 1000x scanning electron microscope micrograph of the alloy obtained in Example 1.
[0031] Figure 3 This is the engineering stress-strain relationship curve of the alloy in Example 1.
[0032] Figure 4 This is the engineering stress-strain relationship curve of the alloy in Example 2.
[0033] Figure 5 This is the engineering stress-strain relationship curve of the alloy in Example 3. DETAILED DESCRIPTION
[0034] The specific technical scheme of the present invention is described in detail below through examples. It should be understood that the following examples can only be used to explain the present invention and cannot be interpreted as limiting the present invention.
[0035] Example 1
[0036] A high thermal conductivity and high plasticity extruded magnesium alloy material and preparation method thereof
[0037] The ratio used in this embodiment is:
[0038] Al 6.0wt%, Zn 2.0wt%, Mn 1.0wt%, RE 4.5wt%, Y 0.5wt%, RE+Y 5.0wt%, the balance is Mg and inevitable impurities. The total amount of inevitable impurities is ≤0.04%; Mn, RE, Y are added in the form of MnCl2, mixed RE, Mg-30%Y master alloy respectively.
[0039] Preparation method:
[0040] (1) Ingredients: Al ingot, Zn ingot, MnCl2, mixed rare earth, Mg-30% Y master alloy and Mg ingot are prepared according to weight percentage and dried in a drying oven. If water vapor is found on the surface, it cannot be put into the furnace; the crucible is cleaned and prepared for loading into the furnace;
[0041] (2) Melting: Set the furnace temperature to 780℃, put in Mg ingots to keep them warm and melt. During the melting process, add a heat preservation cover or other heat preservation devices to prevent heat loss and oxidation. Carefully operate the melting of the charge, and use CO2+SF6 mixed gas for full protection during the melting process. If white smoke and bright light are found, it means the charge is burning, and immediately sprinkle 2# solvent; after the charge is completely melted, remove the surface scum, remove the lower sediment, and evenly sprinkle a layer of 2# solvent on the upper surface to prepare for alloying; during the melting process of the charge, bridging is prohibited, and once discovered, it must be handled in a timely manner;
[0042] (3) Alloying: When the temperature is raised to 750°C, scouring is performed for 3 minutes. Note that the bottom of the pot should be stirred evenly. After scouring, let it stand for 3 minutes, take out samples for spectral analysis, and keep records (including time, temperature, and amount added). According to the results, alloy the ingredients and keep small samples for subsequent re-testing. When the alloy liquid temperature is 750°C, sprinkle the weighed MnCl2 onto the surface of the melt. After the MnCl2 is melted, use a stirring tool to stir while sprinkling No. 2 flux for alloying. Stir for 3 minutes. After the addition is completed, take out samples for spectral analysis and keep records. (including time, temperature, and amount added), and retain a small sample for subsequent retesting; when the alloy liquid temperature is 740°C, place the weighed Al ingot and Zn ingot in the middle of the melt surface to melt, add the Al ingot and Zn ingot, take out the sample for spectral analysis and keep a record (including time, temperature, and amount added), and retain a small sample for subsequent retesting; when the alloy liquid temperature is 760°C, place the mixed rare earth and Mg-30%Y master alloy in the melt to melt, and obtain a rough alloy sample; take out the sample for spectral analysis and keep a record (including time, temperature, and amount added), and retain a small sample for subsequent retesting;
[0043] (4) Refining: Set the refining temperature to 760°C and continue refining for 5 minutes until the alloy liquid becomes shiny after refining.
[0044] (5) Iron reduction: The alloy liquid is cooled to 680-700℃, and a small amount of No. 2 flux is sprinkled into it to cover it while stirring, and the upper surface of the alloy liquid is not damaged as much as possible;
[0045] (6) Standing and casting: After refining, remove the surface scum, evenly sprinkle a layer of 2# flux, stand for 25-35 minutes, and cast after the composition is qualified; clean the inner wall of the mold before casting, and blow it with SF6 for protection; hydraulic dumping should be done slowly so that the liquid flows into the inner shovel of the mold to prevent external debris from hurting people. When the molten liquid flows to the edge of the large diameter, stop casting, and the casting is completed. After the crucible solution is cast, clean the pot and wait for the next pot of smelting;
[0046] (7) Heat treatment: The cast rods were placed in a heat treatment furnace, kept at 350°C for 24 hours, and then air-cooled.
[0047] (8) Extrusion: Use a sawing machine to cut off the loose layer of casting including the head and tail, and use a lathe to turn off the oxide layer on the outer surface of the cast rod. Place it in a heat treatment furnace and preheat it at 300-400°C for 2-4 hours for extrusion. The extrusion ratio is (10-20):1 and the extrusion speed is 0.05-1mm / s.
[0048] Figure 1 and Figure 2 The SEM photo of the extruded magnesium alloy of Example 1 is given. Figure 1It can be seen that a large number of linearly distributed Al-RE phases appear in the extruded structure of the magnesium alloy of Example 1, which are evenly distributed as a whole and have a size of less than 5 μm. This microstructure is conducive to obtaining high plasticity and high thermal conductivity. The thermal conductivity of the extruded magnesium alloy is 112.6 W / (m·K). Figure 3 A typical tensile curve of the extruded alloy is given, and its yield strength, tensile strength and elongation are 206.4MPa, 317.4MPa and 15.5% respectively.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is as follows:
[0051] The ratio used in this embodiment is Al 3.0wt%, Zn 1.0wt%, Mn 0.5wt%, RE 0.5wt%, Y 0.5wt%, RE+Y 1.0wt%, the total amount of inevitable impurities is less than or equal to 0.04%, and the balance is Mg.
[0052] Preparation method step (2) The temperature in the heat treatment furnace during preheating is 220°C, and the preheating is 40 minutes;
[0053] Preparation method step (4) setting the furnace temperature to 750°C;
[0054] Preparation method step (7) The iron reduction temperature is set to 700°C;
[0055] Preparation method step (8) is to stand for 30 minutes, and then prepare for casting after the ingredients are qualified.
[0056] The thermal conductivity of extruded magnesium alloy is 92.4W / (m·K). Figure 4 A typical tensile curve of the extruded alloy is given, and its yield strength, tensile strength and elongation are 203.5MPa, 316.1MPa and 16.5% respectively.
[0057] Example 3
[0058] The difference between this embodiment and embodiment 1 is as follows:
[0059] Al 5.0wt%, Zn 1.5wt%, Mn 0.6wt%, RE 2.0wt%, Y 2.0wt%, RE+Y 4.0wt%, inevitable impurities with a total amount less than or equal to 0.04%, and the balance is Mg.
[0060] Preparation method step (2) The temperature in the heat treatment furnace during preheating is 250°C and the preheating is 45 minutes;
[0061] Preparation method step (4) setting the furnace temperature to 760°C;
[0062] Preparation method step (7) The iron reduction temperature is set to 680°C;
[0063] Preparation method step (8) is to stand for 35 minutes, and then prepare for casting after the ingredients are qualified.
[0064] The thermal conductivity of extruded magnesium alloy is 100.8W / (m·K). Figure 5 A typical tensile curve of the extruded alloy is given, and its yield strength, tensile strength and elongation are 206.5MPa, 311.9MPa and 16.5% respectively.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A magnesium alloy material with high thermal conductivity and high plasticity, comprising the following raw materials in percentage by mass: Al 3.0-6.0wt%, Zn 1.0-2.0wt%, Mn 0.5-1.0wt%, RE 0.5-4.5wt%, Y 0.5-4.5wt%, the balance being Mg and unavoidable impurities; wherein: The total amount of unavoidable impurities is ≤ 0.04%; Mn, RE and Y are added in the form of MnCl2, mixed RE and Mg-30%Y master alloy respectively.
2. The high-strength magnesium alloy material according to claim 1, wherein: The mixed RE has a purity of >99%, and comprises: 35 wt % of La and 65 wt % of Ce.
3. A method for preparing the high thermal conductivity and high strength magnesium alloy material according to claims 1 and 2, comprising: (1) Ingredients: Al ingot, Zn ingot, MnCl2, mixed rare earth, Mg-30% Y master alloy and Mg ingot are prepared according to weight percentage and dried in a drying oven; (2) Melting: Set the furnace temperature to 780°C, put in Mg ingots to keep warm and melt, and after all the charge is melted, remove the scum on the surface, remove the sediment at the bottom, and evenly sprinkle a layer of 2# flux on the upper surface to prepare for alloying; (3) Alloying: When the temperature reaches 750°C, scouring is performed for 3 minutes, and then the mixture is allowed to stand for 3 minutes. When the alloy liquid temperature is 750°C, MnCl2 is sprinkled onto the surface of the melt. After the MnCl2 is melted, 2# flux is sprinkled into the melt while stirring for alloying. The mixture is stirred for 3 minutes. When the alloy liquid temperature is 740°C, Al ingots and Zn ingots are melted in the melt. When the alloy liquid temperature is 760°C, mixed rare earth and Mg-30%Y master alloy are melted in the melt to obtain a rough alloy sample. (4) Refining: Set the refining temperature to 760°C and continue refining the rough alloy sample for 5 min until the alloy liquid becomes shiny; (5) Iron reduction: Cool the refined alloy liquid to 680-700℃, sprinkle a small amount of No. 2 flux to cover it while stirring; (6) Standing and casting: After refining, remove the surface scum, evenly sprinkle a layer of 2# flux, stand for 25-35 minutes, and cast after the composition is qualified to obtain cast rods; (7) Heat treatment: Place the cast rod in a heat treatment furnace, keep it at 350°C for 24 hours, and then air cool it; (8) Extrusion: The air-cooled cast rod is preheated at 300-400°C for 2-4 hours and extruded at an extrusion ratio of (10-20):1 and an extrusion speed of 0.05-1 mm / s to obtain a high thermal conductivity and high strength magnesium alloy material.
4. The preparation method according to claim 3, wherein: The impurity element requirements of the Mg ingot in step (1) are: Fe≤0.004%, Si≤0.03%, Ni≤0.0006%, Cu≤0.002%; The impurity element requirements of Al ingot are: Fe≤0.12%, Si≤0.06%, Ni≤0.015%, Cu≤0.004%; The impurity element requirements of Zn ingot are: Fe≤0.001%, Cu≤0.002%; The impurity requirements for mixed rare earth are: RE≥99%, purity of MnCl2≥96%, Ni≤0.01%.
5. The preparation method according to claim 3, wherein: The drying temperature in step (1) is 200-250° C. and the drying time is ≥30 min.
6. The preparation method according to claim 3, wherein: The entire process of steps (2-6) is protected by a CO2+SF6 mixed gas.
7. The preparation method according to claim 6, wherein: The volume content of CO2 in the mixed gas is 99%, and the volume content of SF6 is 1%.
8. The preparation method according to claim 3, wherein: The 2# flux comprises: MgCl2: 38 ± 3%; KCl: 37 ± 3%; BaCl2: 9±3%; CaCl2: 5±1%; NaCl: 10±3%.
9. The preparation method according to claim 3, wherein: The 2# flux needs to be sieved through a 100-mesh sieve before use, and the sieve rate must be ≥50%.
10. A high thermal conductivity and high strength cast magnesium alloy prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High thermal conductivity magnesium alloys, inverter housings, inverters and automobiles
CN109136699B
High-strength and high-thermal-conductivity magnesium alloy and preparation method thereof
CN116657009A
High-thermal-conductivity and high-strength wrought magnesium alloy and preparation method thereof
CN117026036A